(3TQM bUjOI CfhGQ GdSQGFQ hSQGFQ GdCfhGQs - (3CMeO Hf jhSa Hf eMeO Hf jhSa GdaGSjs; (3JGL GdOjf CHh GdYHGS CMeO Hf eMeO GdHcjQ GdTQjTjs
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGd GdhGMO GdUeO GdYRjR s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf GfJgi hcai hSdGe Ydi YHGOg GdPjf EUWai s
(3bUjOI CfhGQ GdSQGFQ EjVGM Gdecfhf L (B1 (3U`(B144s
(3fSNI KGfjI bUjOI QGFjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B144s
Keywords: (3GdJUha hGdBOGH GdTQYjIs